The Effect of Pectin Concentrations on Characteristics of Brocolli (Brassica oleracea L.) Vegetable Leather - Fauziyah, Annisa Nur; Romalasari, Atika; Ramadhan, Muhammad Gilang (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
This study aimed to determine the effect of pectin concentrations addition on the physicochemical and organoleptic characteristics of broccoli vegetable leather. This study used a completely randomized design (CDR) consisting of 4 different pectin concentration treatments (P0 control, P1 0,5%, P2 1%, P3 1,5%) with 3 replications. Data were analyzed using the One Way ANOVA method followed by Duncan Multiple Range Test (DMRT) at a 5% significance level. The results showed that the increase of pectin concentration affected the physicochemical characteristics (percent elongation, aw, TPT) but did not affect the organoleptic characteristics. The best treatment based on organoleptic characteristics was P1 with a pectin concentration of 0,5% with a yield of 32,57%, percent elongation of 41,33%, pH value of 4,21, aw value 0,67, TPT of 21,5 obrix, and water content of 14,91%.